PENERAPAN ALGORITMA ADVANCED ENCRYPTION STANDARD PADA APLIKASI PENGAMANAN DATA TEKS BERBASIS WEB - Hayon, Elvander; Kristina, Kristina; Darmianto , Amok (LPPM Universitas Widya Dharma Pontianak, 2024)
The continuous development of information technology has an impact on the security of sensitive data and information. Cryptography is one of the relevant techniques to maintain data security and confidentiality. The encryption process converts the original data into an unintelligible format called chipertext, while the decryption process converts the chipertext back into the original data or plaintext. This research designs a cryptographic application using 128 bit AES algorithm to increase the security and trust of users in sending and storing text data. This application helps users protect data and provides a high level of security. The research method used is a literature study. The object-oriented system design analysis technique uses UML to model the system structure. The test results show that the encryption and decryption process runs according to the functionality. Overall, this application can provide confidence to users in securing text data through the encryption and decryption process. This research is expected to be an effective solution for individuals and organizations in maintaining the confidentiality of information. This application is also expected to adapt to the ever-changing development of security technology, so that it remains relevant and effective in the future. Keywords: Cryptography, Advanced Encryption Standard Algorithm, web